2022
DOI: 10.1111/cge.14182
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the clinical spectrum of primary coenzyme Q10 deficiency type 6: The first case with cardiomyopathy

Abstract: We report a 19‐month‐old patient with cardiomyopathy as the first presenting feature of primary COQ10 deficiency‐6. This case expands the phenotypic spectrum of this disorder. Furthermore, it shows that genetic testing for primary COQ10 deficiency should be considered in patients with pediatric‐onset cardiomyopathy as it can guide treatment options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Wang et al [ 69 ] identified two Chinese siblings with COQ10D6 who presented with severe metabolic acidosis, proteinuria, hypoalbuminemia, growth retardation, and muscle hypotonia and died in early infancy (mutations: [c.249C>G] [p.Tyr83Ter] in Exon 2 and [c.1381C>T] [p.Gln461Ter] in Exon 12 of COQ6 ). A 19-month-old patient with cardiomyopathy was found to have the COQ6 variant [c763G>A] [p.Gly255Arg]; the patient died from cardiorespiratory failure before CoQ10 supplementation could be started [ 70 ]. Nam et al [ 71 ] identified 12 children from 11 unrelated Korean families resulting from COQ6 mutations (c.189_191delGAA (p.Lys64del), c.484C>T (p.Arg162*), c.686A>C (p.Gln229Pro), and c.782C>T (p.Pro261Leu)).…”
Section: Clinical Studies Relating To Coq Gene Mutationsmentioning
confidence: 99%
“…Wang et al [ 69 ] identified two Chinese siblings with COQ10D6 who presented with severe metabolic acidosis, proteinuria, hypoalbuminemia, growth retardation, and muscle hypotonia and died in early infancy (mutations: [c.249C>G] [p.Tyr83Ter] in Exon 2 and [c.1381C>T] [p.Gln461Ter] in Exon 12 of COQ6 ). A 19-month-old patient with cardiomyopathy was found to have the COQ6 variant [c763G>A] [p.Gly255Arg]; the patient died from cardiorespiratory failure before CoQ10 supplementation could be started [ 70 ]. Nam et al [ 71 ] identified 12 children from 11 unrelated Korean families resulting from COQ6 mutations (c.189_191delGAA (p.Lys64del), c.484C>T (p.Arg162*), c.686A>C (p.Gln229Pro), and c.782C>T (p.Pro261Leu)).…”
Section: Clinical Studies Relating To Coq Gene Mutationsmentioning
confidence: 99%